Residential outdoor education and environmental attitudes: an examination in a Malaysian University - Md Taff, Md Amin; Aziz, Azlizam; Raja Haron, Raja Nor Safinas; Mohd Rasyid, Nelfianty; Mohd Yasim, Mazuki (2010)
While many outdoor educators are confident their residential outdoor education (ROE) programs improve participants’ environmental attitudes, research findings are inconclusive. This study seeks to examine the effects of a Malaysian university ROE camp on environmental attitudes. A pre and post test approach with non equivalent control group design was utilized among 176 first year undergraduate students. A modified version of CHEAKS and open ended questionnaire were used to gather data from pre and post-tests. Results from ANCOVA procedures suggested that the camp had positively improved the experimental group’s environmental attitudes. Issues of bridging ROE learning outcomes into daily practices are addressed, and a framework for future practice and research is suggested.